Figure 13 in New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora) - Wilbert, Norbert; Song, Weibo (Zenodo, 2005)
Figure 13. Photomicrographs of (A–G) Pithites pelagicus nov. spec., (H, M) Pleuronema coronatum and (I–L) Intranstylum antarcticum nov. spec. after protargol impregnation. (A) Lateral view of the anterior portion; arrows mark the cytopharynx; (B) dorsal side view (looking from ventral to dorsal) of anterior portion, arrow indicates the terminal fragment (''dorsal brush''); (C) ventral view, arrows mark the gap between left and right somatic kineties; (D) ventral view, to show the contractile vacuole pore (arrow); (E) ventral view of apical area, arrows mark the fragment-like perioral kineties; (F) ventral view of a specimen in division; (G) ventral view at a later stage of division, white arrows mark the newly formed oral apparatus in the opisthe, while the black arrow indicates the contractile vacuole pore; (H) left-lateral view, the arrowheads point to the posterior end of paroral membrane, the black arrow indicates whereas the macronucleus; (I, L) stalk, arrowheads in (I) mark the attached diatoms (?); (J) two zooids, arrows indicate the reduced spasmoneme; (K) to show the spasmoneme (arrow); (M) left-lateral view, arrowhead marks the micronucleus, arrows point to the membranelle 3. : Published as part of Wilbert, Norbert & Song, Weibo, 2005, New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora), pp. 935-973 in Journal of Natural History 39 (13) on page 963, DOI: 10.1080/00222930400001509, http://zenodo.org/record/4657793